Comfort and its related factors in Iranian nurses: a cross-sectional study - Zahra Tagharrobi; Leila Ghanbari-Afra; Khadijeh Sharifi; Negin Masoudi Alavi (Scientific Reports)
Abstract This study aimed to investigate comfort and its related factors in clinical nurses working in teaching hospitals of Kashan University of Medical Sciences in Iran. In this cross-sectional study, 300 nurses were selected by stratified random sampling method (2022). Data were collected using the Persian version of the nurse comfort questionnaire and a questionnaire of possible related factors. Data were analyzed using SPSS-16 and One-Way ANOVA, independent t-test, Kruskal-Wallis, Pearson and Spearman-Brown correlation coefficients, and multiple linear regression. On a scale of 30 to 120, nurses’ comfort score was 85.453 ± 11.975 (%95CLM: 84.10-86.81). The simultaneous presence of the variables of interest in nursing, work position, dominant shift, work experience in the current position, length of nursing experience, and education level was significant in the model (F = 32.477, R2 = 0.399, P < 0.0001). Interest in nursing accounted for the largest proportion of variance in comfort (30.2%). The comfort level of clinical nurses working in Kashan teaching hospitals was moderate. It seems that the selection of students and nurses among those interested in the nursing profession will improve the condition of this feeling among working nurses. Additionally, nursing managers need to pay attention to the factors that affect nurses’ comfort in order to improve the quality of nursing care.